PENGARUH SIKAP DAN GENDER TERHADAP PRESTASI BELAJAR PSIKOLOGI MAHASISWA UNIVERSITAS ISLAM IMAM BONJOL PADANG - Sandora, Lisna (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This study aims to determine whether there is a positive and significant influencebetween: 1) attitudes with learning achievement Psychology, 2) gender with psychologylearning achievement 3) attitude and gender together with psychology learningachievement. This research is an ex post facto research with correlational analysis.Population in this research is student of class of 2017 which amounted to 60 people. Theresearch instrument used is documentation for learning achievement, questionnaire forattitudes, and student's personal data for gender. The validity is the validity of theconstructs and the validity of content by expert judgment. The data analysis of the researchresults begins by testing the classical assumption of normality, multicolinearity, andheteroscedasticity test. Also tested the relationship between variables using productmoment correlation. To know the difference of average attitude and learning achievementbetween male students and female students using T-test. The influence of attitude andgender on learning achievement is analyzed by multiple linear regression analysis. Theresults showed that: 1) there was a positive influence and significant attitudes toward theachievement of psychology learning with contribution of significance 0.000 <from 0,05,2)there was no positive and significant influence of gender to student's psychologyachievement because significance value 0,374> 0, 05 and 3) there is a positive influenceand significant attitudes and gender together to student achievement with significancevalue 0,000 <0,05 and contribution of influence of attitude and gender together topsychology learning achievement is 69,8%Keywords: Attitude, Gender, Learning Achievement